Pengaruh Service Level Supplier Terhadap Performance Logistic pada Warehouse di Pt.Xyz Branch Batam - Dannya Fatima H. W; Akmal Suryadi (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
This research analyzes the influence of supplier service quality variables and Transportation Distribution regulations on warehouse performance, influenced by regional regulations. The survey method used in this research is the observation method and data sampling using a questionnaire. Questionnaires were distributed to 25 respondents, these respondents were suppliers who had been selected according to predetermined provisions. Based on the results of the questionnaire regarding supplier locations, it was found that 76% of suppliers were in the Batam area while 24% were outside Batam. Research findings show that supplier service quality has a positive and significant impact on warehouse performance, and improvements in such services can significantly improve warehouse performance. Apart from that, transportation and distribution variables also contribute positively to warehouse performance, and have a positive and significant influence on local government regulations. The positive correlation between local government regulations and warehouse performance shows that managing letter requirements to fulfill these regulations can smooth the flow of goods distribution and increase service levels which will have an impact on warehouse performance..